2021
DOI: 10.1007/s11356-021-13390-y
|View full text |Cite
|
Sign up to set email alerts
|

A comparative analysis of the relationship between innovation and transport sector carbon emissions in developed and developing Mediterranean countries

Abstract: Innovation technologies have been recognized as an efficient solution to alleviate carbon emissions stem from the transport sector. The aim of this study is to investigate the impact of innovation on carbon emissions stemming from the transportation sector in Mediterranean countries. Based on the available data, Albania, Algeria, Bosnia and Herzegovina, Croatia, Egypt, Morocco, Tunisia, and Turkey are selected as the 8 developing countries; and Cyprus, France, Greece, Israel, Italy, and Spain are selected as t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(16 citation statements)
references
References 66 publications
2
14
0
Order By: Relevance
“…These outcomes show the emission reduction potential of increasing the use of renewable energy in the African continent. These results confirm the estimates of Ulucak et al ( 2021 ) and indirectly also those of Demircan et al ( 2021 ), contributing to the discussion around the renewable energy consumption–agricultural carbon emissions nexus. In their recent empirical work, Rahman and Alam ( 2022 ) concluded that renewable energy is seen in innovations that can improve environmentally friendly technologies to reduce carbon emissions and enhance environmental quality.…”
Section: Resultssupporting
confidence: 91%
“…These outcomes show the emission reduction potential of increasing the use of renewable energy in the African continent. These results confirm the estimates of Ulucak et al ( 2021 ) and indirectly also those of Demircan et al ( 2021 ), contributing to the discussion around the renewable energy consumption–agricultural carbon emissions nexus. In their recent empirical work, Rahman and Alam ( 2022 ) concluded that renewable energy is seen in innovations that can improve environmentally friendly technologies to reduce carbon emissions and enhance environmental quality.…”
Section: Resultssupporting
confidence: 91%
“…Industrial production is noticeably more advanced in developed countries than in developing countries (37). For this reason, it has been emphasized that developed countries, especially those with a high use of fossil fuels in production, contribute more to the formation of greenhouse gases on a global scale and cause an increase in Covid-19 cases.…”
Section: Discussionmentioning
confidence: 99%
“…The progress of energy technology has a positive and significant impact on carbon efficiency through the green upgrade of the industrial structure [ 35 ]. (2) The impact of technological innovation on carbon emissions in different industries [ 36 , 37 ]: for example, Erdoğan et al believe that long-term innovation has no significant impact on carbon emissions in energy, transportation, and other industries; the improvement of industrial innovation can reduce carbon emissions, while construction innovation will increase carbon emissions [ 38 ]. (3) The impact mechanism of technological innovation on carbon emissions at different scales [ 39 , 40 , 41 ]: for instance, Obobisa et al used panel time series data from 2000 to 2018 to examine the impact of green technology innovation on CO 2 emissions in 25 African countries.…”
Section: Literature Reviewmentioning
confidence: 99%